The Effects of Different Materials and Geosynthetics on Embankment Safety and Behavior - Elif Çiçek (Doğal Afetler ve Çevre Dergisi)
In this study, road embankment models constructed with new materials obtained from the recycling of natural and waste materials were analysed using the finite element method. The effects of different materials such as sandy silt, rock aggregate, concrete, glass on the road fill were investigated and the results of the analysis of the models using waste fibers in the road fill were compared with the natural conditions. In addition, calculations have been made for road embankment models which are tried to be reinforced with different numbers of geosynthetic reinforcement. Thus, the effects of different materials, fibers and geosynthetics on the number of safety of the road model created were examined. Evaluations were made against the collapse of the road and the effects of the consolidation behaviour arising from groundwater under filling were compared for different material conditions. In addition, the residence differences that may be caused by traffic load in different parts of the road in the fillings constructed using different materials were evaluated and the effects of geosynthetics were tried to be determined. When the results were examined, evaluations were made for both environmental and more efficient solutions. It has been observed that the materials obtained by recycling of waste materials can make significant contributions to the stability and safety of road embankments.